Intersecting Identities and Nonsuicidal Self-Injury among Youth. Issue 2 (3rd April 2021) - Angoff, Harrison D.; McGraw, James S.; Docherty, Meagan
ABSTRACT: Recent research suggests that intersecting marginalized identities may be important in explaining suicide-related mental health disparities. However, inconsistent findings have emerged regarding nonsuicidal self-injury (NSSI). Guided by an intersectionality framework, we examined relations between identity and NSSI using a representative sample of 8th through 12th graders from Utah (N = 49, 425). The independent influence of sexual orientation, gender, race/ethnicity, and religious preference on NSSI were examined using bivariate and multivariate logistic regression analyses. Intersectionality analyses, using two-way interaction terms, were then conducted to examine the impact of intersecting identities on NSSI. Results indicated that gay/lesbian, bisexual, and transgender and "other" gender youth, and non-Latter-day Saint (LDS) participants were at particularly high risk of NSSI. In intersectionality analyses, sexual minorities were more likely than heterosexual participants to endorse NSSI among cisgender, but not gender minority youth; bisexual participants of color were less likely to engage in NSSI than European American bisexual youth, but no effect for race/ethnicity was found for gay/lesbian youth; and among heterosexual participants, non-LDS youth were more likely than LDS youth to engage in NSSI, but no effect for religion was found among gay/lesbian or bisexual participants. Implications of these results and the differences in results by method are discussed.